EFFECTIVENESS OF INFORMATION COMMUNICATION TECHNOLOGIES AND THEIR USE IN PRIMARY CLASS EDUCATION (Academia Science Repository, 2023)
This article provides examples of the use of information and communication technologies in mother tongue and reading literacy classes for primary school students, from which students of primary education and teachers can use.